2023
DOI: 10.1186/s12872-023-03054-9
|View full text |Cite
|
Sign up to set email alerts
|

3-Year outcomes after left atrial appendage closure in patients with nonvalvular atrial fibrillation: cardiomyopathy related with increased death and stroke rate

Abstract: Introduction Left atrial appendage closure (LAAC) is a novel treatment for stroke prevention in high-risk patients with non-valvular atrial fibrillation (NVAF). However, the long-term outcomes after LAAC in Chinese NVAF patients are still lacking. Methods This was a single-center, bidirectional, nonrandomized registered study. Patients who underwent LAAC implantation from May 2014 to April 2021 in a large Chinese center were enrolled. The primary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This study’s comprehensive evaluation of percutaneous left atrial appendage (LAA) closure using various occluder devices at our center from 2009 to 2023 underscores the procedure’s efficacy and safety in patients with nonvalvular AF who are contraindicated for or intolerant to oral anticoagulation therapy. Continuous improvements in the LAAC procedure and device technology have significantly contributed to the procedural safety and efficacy, as evidenced by the consistent high success rates in major trials such as PROTECT (90.9%), CAP (94.4%), PREVAIL (95.1%), CAP2 (94.8%), and EWOLUTION (98.5%) [ 9 ]. The overall procedural success rate of 95.7% in our study showed no significant difference between devices, demonstrating the technical feasibility of LAA closure across different device generations.…”
Section: Discussionmentioning
confidence: 99%
“…This study’s comprehensive evaluation of percutaneous left atrial appendage (LAA) closure using various occluder devices at our center from 2009 to 2023 underscores the procedure’s efficacy and safety in patients with nonvalvular AF who are contraindicated for or intolerant to oral anticoagulation therapy. Continuous improvements in the LAAC procedure and device technology have significantly contributed to the procedural safety and efficacy, as evidenced by the consistent high success rates in major trials such as PROTECT (90.9%), CAP (94.4%), PREVAIL (95.1%), CAP2 (94.8%), and EWOLUTION (98.5%) [ 9 ]. The overall procedural success rate of 95.7% in our study showed no significant difference between devices, demonstrating the technical feasibility of LAA closure across different device generations.…”
Section: Discussionmentioning
confidence: 99%